2022
DOI: 10.25367/cdatp.2022.3.p97-103
|View full text |Cite
|
Sign up to set email alerts
|

3D garment fit on solid and soft digital avatars – preliminary results

Abstract: For a holistic assessment of the interaction between the human body and tight fitted clothing, it is necessary to consider the mechanical properties of the body. Default avatars in CAD software are usually solid and do not take this interaction into account. For this purpose, a solid avatar is converted to a deformable one by using the soft body physics implementation in the simulation program Blender. The fit of a 3D garment on both avatars are compared, which allows a first evaluation of the differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The application of diverse athletic body movements was not very complicated using a combination work process of 3D body-scanned data, Adobe Mixamo and CLO 7.0. Also, 3D body scan data has been considered a useful tool in creating precise body figures reflected with the actual human body, and hence, several research experimented with virtual fit using 3D body scan data (Brake et al ., 2022; Choi and Hong, 2015; Lee et al ., 2015; Wu and Kuzmichev, 2021). However, the application of rigging animation in 3D body scan data caused different body shapes from actual moving bodies.…”
Section: Resultsmentioning
confidence: 99%
“…The application of diverse athletic body movements was not very complicated using a combination work process of 3D body-scanned data, Adobe Mixamo and CLO 7.0. Also, 3D body scan data has been considered a useful tool in creating precise body figures reflected with the actual human body, and hence, several research experimented with virtual fit using 3D body scan data (Brake et al ., 2022; Choi and Hong, 2015; Lee et al ., 2015; Wu and Kuzmichev, 2021). However, the application of rigging animation in 3D body scan data caused different body shapes from actual moving bodies.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainability initiatives, focused on reducing garment returns, are hampered by landmarking and measuring practice leading to the comparison of cross-sectional planes (size chart girths) at different skeletal heights. Further, with current study demonstrating the necessity for accurate humanoid soft body physics to achieve a realistic simulation of the humanoid-to-coveroid interaction [41], the need to begin with an accurate body model is paramount. The need for change within established apparel practice is urgent [10,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…• 4D study and solving known challenges with polygon division for mesh segmentation on the homologous mesh [41]; • improving the accuracy of parametric humanoids that often display unrealistic body-shape [42];…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, investigations have shown that the distortions show angular and unnatural deformations under strong pressure. [7] 2. Soft Tissue…”
Section: Soft Avatars In Clothing Cadmentioning
confidence: 99%